2012
DOI: 10.5999/aps.2012.39.6.659
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Assisted Lipotransfer for the Treatment of Parry-Romberg Syndrome

Abstract: Progressive facial hemiatrophy, also known as Parry-Romberg syndrome, is a progressive and self-limited deformation of the subcutaneous tissue volume on one side of the face that creates craniofacial asymmetry. We present the case of a patient with a five-year history of progressive right facial hemiatrophy, who underwent facial volumetric restoration using cell-assisted lipotransfer (CAL), which consists of an autologous fat graft enriched with adipose-derived stem cells (ASCs) extracted from the same patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 12 publications
1
43
0
5
Order By: Relevance
“…Otro trabajo en base a 1 caso publicado en México, con enfermedad de Parry-Romberg al que se le aplicó lipoinjerto enriquecido con ADSC, muestra permanencia del lipoinjerto a los 12 meses de seguimiento (17).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Otro trabajo en base a 1 caso publicado en México, con enfermedad de Parry-Romberg al que se le aplicó lipoinjerto enriquecido con ADSC, muestra permanencia del lipoinjerto a los 12 meses de seguimiento (17).…”
Section: Discussionunclassified
“…Encontramos también 2 publicaciones de casos clíni-cos (17,18), ambos con nivel de evidencia 4, que simplemente ilustran el uso de ADSC en patologías como la esclerodermia lineal (deformidad en cup de sabre) y en latitudes tan diversas como México y Turquía; no obstante no permiten establecer conclusiones por tratarse de casos aislados.…”
Section: Discussionunclassified
“…Although lipotransfer supplemented with ASCs or SVF cells have shown therapeutic potential in uncontrolled trials and comparative case series, [16][17][18][19][20][21][22] the clinical results remain controversial. Recently, some comparative studies of cell-assisted lipotransfer were reported.…”
Section: Clinical Reports Of Cell-assisted Lipotransfermentioning
confidence: 99%
“…Castro-Govea et al (20) also reported one case using CAL to treat patients with mild and moderate Parry-Romberg syndrome using computed tomography with three-dimensional reconstruction. The postoperative evolution of those patients in the short-and longterm (one and 12 months, respectively) was satisfactory.…”
Section: Cal For Clinical Treatment Of Facial Deformitymentioning
confidence: 99%
“…Fournier (28), Donofrio (29) and others have contributed to our collective understanding of periorbital aging and have appropriately emphasized the importance of volume preservation in our surgical techniques and illustrated the success of volume restoration using fat. Currently, there is a better understanding of the need for the restoration or adjustment of facial volume (30), and that the revascularization of a small graft is Parry-Romberg syndrome 1 1 to 12 Castro-Govea (20) superior to that of a large graft (31). For these reasons, a technique has been developed whereby fat is harvested and injected through a blunt cannula with minimal vacuum to prevent explosion of the cellsupplemented fat.…”
Section: Injection Of Ascs and Svf Into Target Sitesmentioning
confidence: 99%